Fatwa MUI tentang Produk Israel (Mendukung Israel dan Mendukung Produk yang Dukung Israel Haram) - Assegaf Gavlek; Sutopo, Sutopo (HOKI : Journal of Islamic Family Law, 2024)
The Indonesian Ulema Council (MUI) is an organization that can provide advice and suggestions regarding legal, religious and social issues, through its product called fatwa. Even though MUI fatwas do not have the same position as positive law which has binding power for all citizens, MUI fatwas can or can have binding power after first being transformed into statutory regulations. In fact, the fatwas produced by the MUI have made a positive contribution to the Indonesian regulatory system, both in criminal and civil law. The existence of MUI fatwas has become the most important part of the national legal system within the framework of the Unitary State of the Republic of Indonesia which is based on the first principle, namely Belief in One Almighty God and one of the living laws is Islamic law. However, it is felt that the authority of fatwas has not yet received its proper place and position in national and state life, and even MUI fatwas are still being debated and considered cynical.